Study of Malnutirtion in Children below 5 years in SulaimanyaCity - A. hadi Al-saady, Ali (Tikrit Journal of Pharmaceutical Sciences, 2023)
Study of malnutrition (underweight & overweight) in children under 5 years in that area & its relation to different variables (Age, Sex, Type of milk feeding, Time of introduction of complementary feeding, maternal education and previous hospital admission). The sample was collected randomly from 4 primary health care centers in Sulaimany city between (July - 2005) to (January - 2006). The total no. of children suweyed were 456, 256 (65.I o/o) were (male), 200 (43.9%) were (female). Stunting, wasting & underweight were reported in 6.3Yo , 6.lyo ,lI.Iyo respectively ,while rate of obesity and overweight werc 7.6Yo ,3.syo respectively. A statistically significant association was noted between various forms of malnutrition and age implying an increase prevalence of stunting after the 2nd year of life and increase in prevalence of underweight during the I't y.ut of lif", while obesity and overweight clustered in the age range (4-5 yrs). Malnutrition also have high association with level of maternal education , higher prevalence of malnutrition( stunting ,wasting ,underweight) in illiterate mothers & lowest in highly educated ,while prevalence of over nutrition (obesity & overweight) were more in highly educated mothers and least in illiterate ones. The nutritional status of children under 5 years in Sulaimany city seems to be satisfactory except for moderately high prevalence of wasting which requires further support to the child health through continuing the nutritional support offered to that area and promotion of maternal education regarding child health and nutrition.